ALTERNATIF MODEL PEMBELAJARAN MENYIMAK BAHASA KEDUA/ASING LEVEL DASAR - Nurchasanah (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2015)
Abstract: Most people considered that proficient in a language meant fluent in speaking. The speaking skills were always related to the listening skills. Without having good listening skills, anybody’s speaking skills would not be perfect. Therefore, the listening skills were needed in order to achieve the perfection of other language proficiency. To achieve the listening skills, especially listening to the second or foreign language on basic or beginner level, there were several alternative teaching and learning model which could be implemented. The alternative models were classified into several points of view. Determining the proper teaching and learning needed skills in choosing by considering the purpose of the listening teaching and learning, the students’ scheme, the text’s conditions, and the development of the students’ cognitive. Abstrak: Sebagian besar orang menganggap bahwa mahir berbahasa berarti mahir berbicara. Keterampilan berbicara selalu terkait dengan keterampilan menyimak.Tanpa berbekal keterampilan menyimak yang bagus, keterampilan berbicara seseorang tidak akan sempurna. Karena itu, keterampilan menyimak sangat diperlukan demi kesempurnaan keterampilan berbahasa yang lain. Untuk mencapai kompetensi menyimak, khususnya menyimak bahasa kedua/asing pada level dasar atau pemula, ada berbagai alternasi model pembelajaran yang dapat diterapkan. Alternasi model pembelajaran yang dimaksud terklasifikasi atas beberapa sudut pandang. Untuk menentukan model pembelajaran yang tepat, diperlukan kecakapan dalam memilihnya dengan mempertimbangkan tujuan pembelajaran menyimak, skema siswa, kondisi teks, dan perkembangan kognisi siswa.